KORELASI MAQẢSHID AL-SYARỊ’AH DENGAN METODE PENETAPAN HUKUM - Idrus, Achmad Musyahid (DIKTUM: Jurnal Syariah dan Hukum, 2014)
Maqashid al-Syariah is known as a method of Islamic law philosophy. It put a reason to explore the inner meaning of the text by connecting reality that appeared arround it. Meanwhile, the method of decision law is one way to find and act the law among the people. Maqashid syariah and method of decision law has corelation to fulfill the ideal meaning of law in the text and in other way, maqashid syariah purposes to realize the maslahat for peoples.